Four variations on fair wages and the Phillips curve - Andrea Vaona (Kiel Institute for the World Economy (IfW), 2011)
The present paper explores the connection between inflation and unemployment in different models with fair wages both in the short and in the long runs. Under customary assumptions regarding the sign of the parameters of the effort function, more inflation lowers the unemployment rate, though to a declining extent. This is because firms respond to inflation - that spurs effort by decreasing the reference wage - by increasing employment, so to maintain the effort level constant, as implied by the Solow condition. Under wage staggering this effect is stronger because wage dispersion magnifies the impact of inflation on effort. A stronger effect of nflation on unemployment is also produced under varying as opposed to fixed capital, given that in the former case the boom produced by a monetary expansion is reinforced by an increase in nvestment. Therefore, we provide a new theoretical foundation for recent empirical contributions finding negative long- and short-run effects of inflation on unemployment.
Keywords: E3; E20; E40; E50; 330; Efficiency wages; money growth; long-run Phillips curve; trend inflation; wage staggering; Phillips-Kurve; Effizienzlohn; Geldmenge; Inflation; Trend; Lohnrigidität; Theorie